Efektivitas Model Pembelajaran Contextual Teaching and Learning terhadap Kemampuan Koneksi Matematis Siswa Madrasah Ibtidaiyah - Pauziyah; Imran; Susy Pransiska (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
This study aims to determine the effect of the Contextual Teaching and Learning (CTL) model on the mathematical connection ability of fourth-grade students at Madrasah Ibtidaiyah. Mathematics learning in elementary schools often emphasizes memorization of formulas and procedures, causing students difficulties in connecting mathematical concepts with everyday life. Therefore, an innovative learning model is needed to create meaningful learning experiences. This research employed a quantitative approach using a pre-experimental design with one group pretest-posttest. The subjects of this study were fourth-grade students of MI Rahmatullah Jambi City. Data collection techniques included observation, interviews, documentation, and tests. The results showed that the implementation of the CTL model improved students’ mathematical connection abilities. The average pretest score was 68, while the posttest score increased to 86. The N-Gain result was 0.61 in the moderate category. These findings indicate that the CTL model effectively enhances students’ mathematical connection abilities because students are directly involved in relating mathematical concepts to real-life situations